Imperfect monitoring, cyclical, and learning model perspectives: Price war in the Indonesian lighting industry - Edwinarto, Dominicus (International Journal of Engineering and Technology, 2018)
In marketing terms, the phenomenon of price war is regarded as the result of over-competition and retaliatory reaction in order to win market share. Based on the available literature, three refined models of price war antecedents has been identified: the imperfect monitoring model, the cyclical model, and the learning model. This article was written as part of a recent empirical observation of four Indonesian lighting companies who consider themselves to be currently engaged in price war. Based on the proposition made earlier by Heil and Helsen (2001), this study was prepared as a qualitative survey using an open-ended questionnaire method. The study found that price war is a result of competitive interaction in periods where demands are declining and induced by intra-brand competition. In conclusion, propositions to manage activities in conditions of price war are presented.Â Â